A rare case of Atrial Myxoma presenting as stroke in a young female patient - Khan, Amir; Regmi, Shyam Raj; Dahal, Pravakar (Nepalese Heart Journal, 2022)
Atrial myxoma is one of the most common benign tumor of heart occurring mostly in left atrium. Cerebral embolization is one of the serious complication of left atrial myxoma. Stroke in young patient is a rare condition which may be overlooked in the absence of any history of cardiac problems and diagnosis may be delayed until there is functional impairment as in the case we reported here in 25 years old female. The clinical presentations along with appropriate investigations and treatment are discussed here.